What Surah Al-Kahf Says About Students' Rights And Obligations - Muazzen Muazzen (Al-Thiqah: Journal of Hadith and Prophetic Tradition, 2025)
This research aims to determine students' rights and obligations by analyzing Surah al-Kahf. This research uses a library-based analysis. This research utilizes original data sources from The Qur'an commentary books. The study results imply that students have various rights and obligations to the education process. Students have the right to an all-encompassing education, the independence to choose and evaluate their teachers, and the possibility to actively acquire new knowledge. Students have a variety of obligations, including the requirement to make sacrifices to further their education, the responsibility to adhere to the instructions of teachers, the commitment to fulfill study contracts, and the duty to maintain an atmosphere conducive to learning activities.